FAKTOR PENENTU MINAT MAHASISWA AKUNTANSI BERKARIER SEBAGAI AKUNTAN PUBLIK - Nova Ayu Damayanti, 13.05.52.0116; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2017)
Some types of careers that can be run by accounting students after becoming a graduate are as a Public Accountant, Educator Accountant, Corporate Accountant, Government Accountant, and others. The purpose of this research is to know the interest of accounting career students as public accountant based on the factors of financial reward, professional training, professional recognition, social values, work environment, job market consideration, and personality. This study was conducted on accounting students who are in UNDIP, UNNES, UDINUS, and UNISBANK with the number of respondents as many as 150 people. The data used in this study is the primary data obtained through the distribution of questionnaires. This study uses multiple regression analysis with the aim to find out how the factors that influence the interest of accounting students as a career accountant public. The results of this study indicate professional training, professional recognition, work environment, job market  considerations, and personalities have a significant positive effect on the interest of accounting students as a career accountant public. Social Values positively insignificant effect on the interest of accounting students career as a public accountant. While the financial rewards negatively affect no significant interest in accounting students career as a public accountant.Keywords: Financial Awards, Professional Training, Professional Recognition, Social Values, Work Environment, Job Market Considerations, and Personalities